uno lo interiorizó, lo aplicó, lo practicó, y lo puedo llevar como aporte a mis estudiantes: desarrollo de competencias socioemocionales en docentes de preescolar a través de la educación experiencial virtual (2020)
This thesis's objective was to design a training program that uses virtual experiential education to teach and develop three social-emotional competencies (SEC) in preschool teachers: emotional recognition, emotional regulation, and frustration management. Likewise, we made an analysis and evaluation of this training to analyze its effectiveness and scalability since the aim is that this could be a public policy proposal in the medium term. This study sought to answer the following research questions: how involved were the participants in the training activities? How are the teachers applying the learning from the training in their classrooms? How much do the participants put into practice the SECs worked on in the course in their daily lives? What adjustments should we make to the proposed training? And how scalable is the procedure? Similarly, for the sampling, a selection was made for convenience. There were 20 preschool teachers, all female, who ranged in age from 20-56, and at the time of the research, worked in six public schools in Bogotá. However, the procedure consisted of a virtual course carried out through a virtual blog and whose objective was to promote the SECs mentioned above through virtual experiential education. The results suggest average participation of 86%. Also, it was evident how the teachers put into practice the SECs worked in the course. Finally, we found that the teachers took the methodology and contents of the study to their classrooms and their personal, family, and academic spheres.